As contribuições das oficinas temáticas ambientais na formação de alunos do curso normal médio e nos anos iniciais do ensino fundamental - Silveira, Marlise Grecco de Souza (2014)
The environmental issue is an ever present concern throughout society and education is seen as essential to change this scenario materialize. Thus, the Environmental Education (EE) is an essential component of national education and must be present at all levels and modalities of the educational process. This dissertation deals with the EE in the school context and attempts to ascertain the contributions of environmental thematic workshops with student's Normal Course and in the Early Years of basic education. This work was divided into two phases. In the first phase were provided four thematic workshops on EE to 57 students only school in the municipality of Uruguaiana-RS that has the Normal Course as a teaching modality and also before and after activities, a questionnaire was applied in order to verify the knowledge students about EE and assess whether the proposed training was effective in their formation. In the second phase a workshop, which had as its theme the construction of educational games using recyclable and reusable materials, with 60 students of the Early Years of elementary school three local schools that have low performance in the Index of Basic Education Development was held. In addition, through mental maps the children's perceptions of the environment were analyzed. The results showed that students who participated of four thematic workshops performed better at posttest raising your batting average in the questionnaire, given that it can be inferred that the thematic workshops potentiated the student s knowledge of the EE. In the second phase, students in the Early Years were mostly comprehensive and environmental perceptions about the environment and after the implementation of the thematic workshop these perceptions were more frequent signaling that there was an expansion of student s knowledge about the environment. After the execution of the works that made up this dissertation is concluded that the proposed methodology was effective because the thematic workshops presented contributions in training students for the environmental issues can be facilitators and teaching resources for EE in the school context.